Lexical Ambiguity in the “The Merry Adventures of Robin Hood” Novel by Howard Pyle - Arief Hadziq Fikri; Rio Rizky Octora (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2023)
This study aims to find the types and amount of Lexical Ambiguity in the novel